Estudo da cristalização de nanopartículas de NiO por difração e absorção de raios-X - Meneses, Cristiano Teles de (2007)
Techniques of structural characterization, in particular X-ray absorption Spectroscopy (XAS) and X-ray Diffraction (XRD) were applied to study the crystallization of NiO nanoaprticles. In the first part of the work we study the process of crystallization of NiO nanoparticles (NP's) growing from a low cost method, in different physics and chemical condition (concentration of the organic precursor, synthesis time and temperature). The method is based on a gelatin solution with nickel chloride. The effect of the pH was studied with the addition of NaOH (in the precursor solution of the NP's). These results showed a reduction in the particle size with the increase of pH and change particle shape from pyramidal (low pH) to almost spherical (high pH) observed by scanning electronic microscopy (SEM). Rietveld refinement has been applied to all X-ray powder diffraction patterns. Calculated results using Scherrer equation had shown particles with sizes great than 5nm. In the second part of the work we study in situ the process crystallization and growth of NiO NP's. The effect of the heating rate in the formation and growth of particles have been done. These results showed that the increase of the heating rate delays the formation of the NiO NP’s and reduces the particles size. We realize also comparative study through the experimental results X-ray Absorption of rays-X next edge (XANES) and ab initio calculations using a multiple-scattering model (code Feff 8).